Preeclampsia Screening Using The Smartphone Method: Literature Review - Desriva, Nia; Bin Sansuwito, Tukimin; Dioso, Regidor III (International Journal of Health Sciences, 2023)
Introduction: Indonesian maternal mortality in 2012, 32.5% was caused by hypertension, preeclampsia, and eclampsia, while 24.22% in 2015 and 26% in 2016. Currently, there is no method of screening for preeclampsia based on maternal characteristics that were carried out during the first visit antenatal. The use of technology has great potential to improve health care at the community, especially in low-middle income countries. It is necessary to make a breakthrough in the form of developing a screening model for preeclampsia by utilizing information technology. Material and Methods: This type of research uses literature study method sourced from journals and publications results. Population in This research is all journals and article obtained from Pubmed, Clinical Key, Science direct, Google scholar with PRISMA design. Results:. As a result of the 5 articles found, it was stated that there was an effect of testing an Android-based preeclampsia screening application that could detect it effectively The early risk of preeclampsia was shown by all midwives who were part of the application trial sample stated that an Android-based preeclampsia screening application for pregnant women ≤ 20 weeks was feasible to use. Conclusion:. The use of the application is quite good for community-based preeclampsia screening